Penerapan Teori Belajar Behaviorisme dan Belajar Kognitif Sosial Albert Bandura di Sekolah - Habsy, Bakhrudin All; Salsabila, Adinda; Husna, Aulia Mustafida; Putri, Dwi Ajeng Mareta (Lembaga Yasin AlSys, 2024)
Learning theory is a set of interrelated general principles and explanations of certain facts and findings relating to learning events. There are some theoretical perspectives of learning known in educational psychology. Each of these perspectives sees learning as individual change, but each has a different focus and importance. The method used in this article is qualitative descriptive method by conducting document research analysis. Here we conduct research based on previous research publications/references that have been uploaded in scientific journals and contain theories related to the discussion of research. The purpose of this study is to describe the application and implications of behaviorism learning theory and Bandura's social cognitive learning theories in school learning. The behavioral learning theorem emphasizes learning as visible and observable behavioural changes influenced by the external environment to human behaviour. The differences between the different learning theory characteristics are due to the different kinds of learning that are studied.